The level of readability of the functional Arabic book for non-native speakers At Al al-Bayt University - Al-Khaza'leh, Sami Tawfiq Jamil (Journal of Educational and Psychological Sciences, 2021)
This study aimed to measure the level of readability of functional Arabic textbook for non-native speakers of Al-Bayt University. And to identify the order of the text of the book according to the degree of readability. The study relied on the completion test in order to achieve its goal. The test was applied to three texts from the book. The test was distributed on an intentional sample made up of (33) learners from advanced level learners in the Language Center, Department of Arabic Language for Non-Native Speakers. The results of the study revealed that the learners ’responses to the complementarity test were at the frustrating level of the three texts, where the number of students at this level reached (13) with a percentage (39.4%). The results of the study also showed that the reading texts were not graded according to the level of legibility.